Statistical analaysis for removal of Cadmium from aqueous solution at High pH - Kabbashi, Nassereldeen Ahmed; Daoud, Jamal Ibrahim; Mirghani, Mohamed Elwathig Saeed; Rosli, Nurhasni Falina (INSI Publications, 2011)
In the view of Cadmium (Cd) toxicity from human health, heavy metal concentrations in water are controlled by strict standards and should be reduced to the standards permitted. This study is concerning an approach of removing a heavy metal, Cd, from its aqueous solution by carbon nanotubes (CNTs) absorption. The synthetic water was prepared with initial Cd concentrations of 1mg/L and shook with CNTs, before the water is separated by filtration. A spectrophotometer procedure was applied to analyze the filtrate for the concentration of Cd. The effects of the varying factors on the Cd removal efficiency, which are the CNT dosage, pH, agitation speed and contact time, were studied. All of the factors used in the adsorption experiment were said to be significant with the adsorption capacity which has been identified from the regression analysis. From the results obtained, the highest percentage removal of Cd using CNT is at pH7, 10 mg of CNTs dosage, contact time of 120 min and agitation speed of 150 rpm which gave 19.14% removal.